Analysis of verbal and nonverbal communication and enactment. the processing issues COST 2102 International Conference, Budapest, Hungary, September 7-10, 2010, Revised Selected Papers - Esposito, Anna; Vinciarelli, Alessandro; Vicsi, Klára; Pelachaud, Catherine; Nijholt, Anton (Springer eBook., 2011)
This volume brings together the advanced research results obtained by the European COST Action 2102 "Cross Modal Analysis of Verbal and Nonverbal Communication", primarily discussed at the PINK SSPnet-COST2102 International Conference on Analysis of Verbal and Nonverbal Communication and Enactment: The Processing Issues, held in Budapest, Hungary, in September 2010. The 40 papers presented were carefully reviewed and selected for inclusion in the book. The volume is arranged into two scientific sections. The first section, Multimodal Signals: Analysis, Processing and Computational Issues, deals with conjectural and processing issues of defining models, algorithms, and heuristic strategies for data analysis, coordination of the data flow and optimal encoding of multi-channel verbal and nonverbal features. The second section, Verbal and Nonverbal Social Signals, presents original studies that provide theoretical and practical solutions to the modelling of timing synchronization between linguistic and paralinguistic expressions, actions, body movements, activities in human interaction and on their assistance for an effective human-machine interactions.